1998
DOI: 10.1039/a704640e
|View full text |Cite
|
Sign up to set email alerts
|

Three-center intramolecular hydrogen bonding in oxamide derivatives. NMR and X-ray diffraction study

Abstract: This contribution describes the synthesis and structural investigation of the symmetric and nonsymmetric oxamides N,N Ј-bis(2-hydroxyphenyl)oxamide 1, N,N Ј-bis(5-tert-butyl-2-hydroxyphenyl)oxamide 2, N,N Ј-bis(3,5-dimethyl-2-hydroxyphenyl)oxamide 3, N,N Ј-bis(2-hydroxybenzyl)oxamide 4, N,N Ј-diphenethyloxamide 5, N-(2-hydroxyphenyl)-N Ј-(2-methoxyphenyl)oxamide 6, N-(2-hydroxyphenyl)-N Ј-phenethyloxamide 7, (1S,2R)-(؊)-N-(2-hydroxyphenylcarbamoylcarbonyl)norephedrine 8, (1R,2S)-(؊)-N-(2-hydroxyphenylcarbamoyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
65
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 12 publications
(22 reference statements)
9
65
0
Order By: Relevance
“…Results are listed in Table 3 In oxalamate and bis-oxalamide systems, the participation of C(6)-H6⋅⋅⋅OCNH hydrogen bonding as a cooperative interaction in THB formation, has been noted in both solution and in the solid state. 18 In solution, the δH(6) is shifted to high frequencies by the local deshielding effect of the amide carbonyl group, which is most of the time pointing out to this hydrogen atom as the N-H mobility is smaller. This effect has been known for a long time for ortho-substituted anilides.…”
Section: Solvent Effects On Solution Conformationmentioning
confidence: 99%
See 1 more Smart Citation
“…Results are listed in Table 3 In oxalamate and bis-oxalamide systems, the participation of C(6)-H6⋅⋅⋅OCNH hydrogen bonding as a cooperative interaction in THB formation, has been noted in both solution and in the solid state. 18 In solution, the δH(6) is shifted to high frequencies by the local deshielding effect of the amide carbonyl group, which is most of the time pointing out to this hydrogen atom as the N-H mobility is smaller. This effect has been known for a long time for ortho-substituted anilides.…”
Section: Solvent Effects On Solution Conformationmentioning
confidence: 99%
“…In this solvent, temperature gradient values of amide N-H chemical shift (∆δ/∆T) below 2 ppb are considered as indicative of solvent shielded or non-exposed systems. 17 Alternatively, for small systems ∆δ/∆T values, 18 as well as solvent induced gradients of the NH chemical shift and N-H IR stretching frequencies 12 have been related to the strength of the three centered hydrogen bonding interaction, however, the energy involved has not been estimated. Our previous studies on oxalamide derivatives have demonstrated the existence of THB both in DMSO solution 1 and in solid state 18 and have also established the role of tautomeric equilibria on the stability of these systems.…”
Section: Introductionmentioning
confidence: 99%
“…2 The existence of three-center H-bond interactions in solution has also been experimentally demonstrated. 3 Two types of three-center H-bond interaction can be distinguished: ͑a͒ one that involves an H atom and two acceptor atoms ͑denoted A 1 HA 2 ), and ͑b͒ one that involves an acceptor atom and two H atoms ͑denoted H 1 AH 2 ). 4 These two possibilities are depicted in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental and theoretical studies have demonstrated that intramolecular hydrogen bonds in oxalamides determine their geometry and conformation whereas intermolecular hydrogen bonds increase their stability. [1][2][3] Due to these interactions, oxalamides are applied in diverse areas such as artificial receptors for biological recognition, 4 in engineering and crystal design 5 and in organogels formation. 6 Recently, oxalamide derivatives were identified as HIV-1 inhibitors.…”
Section: Introductionmentioning
confidence: 99%